Dark Pattern Marketing Practices and their Impact on Consumer Trust and Decision-Making - Jaiswal, Trapti (International Journal of Engineering and Management Research, 2026)
Dark pattern marketing practices refer to deceptive digital design techniques that influence consumers to make decisions they might not otherwise choose. With the increasing use of online platforms, such practices have become common in digital marketing environments. This study examines how dark pattern marketing practices affect consumer trust and decision-making. Existing research shows that techniques such as hidden costs, misleading scarcity, and forced continuity reduce consumer autonomy and create confusion during online transactions. The literature further indicates that while dark patterns may increase short-term conversions, they negatively impact consumer trust and long-term brand relationships. Studies also highlight that many consumers remain unaware of these practices, making them more vulnerable to manipulation. Overall, the findings suggest that dark pattern marketing practices pose ethical challenges and emphasise the need for transparent marketing strategies and stronger regulatory oversight to protect consumer trust in digital marketplaces.